Unsung Hollywood musicals of the golden era 50 overlooked films and their stars, 1929-1939 - Bradley, Edwin M. (McFarland & Company, Inc., Publishers, 2016)
"This book takes a look at the unsung songfests of the '30s...secondary or forgotten features with short-lived or unlikely stars from major studios and Poverty Row. Through analysis of films the author profiles performers. Behind-the-scenes figures are discussed. Filmographies and production information are included, with background on key participants"...